Collective foresight and intelligence for sustainability - Sylvia L. R. Wood; Amy Luers; Jennifer Garard; Ajay Gambhir; Kalpana Chaudhari; Maria Ivanova; Casey Cronin (Global Sustainability, 2021)
Non-technical summary Charting robust pathways towards more sustainable futures that ‘leave no one behind’ requires that diverse communities engage in collective foresight and intelligence exercises to better understand global systemic challenges, anticipate the emerging risks and opportunities that disruptions present, and share perspectives on how to respond and inform decision-making. We report on the recent use of an international rapid foresight survey to assess expected societal trends over the next 3 years following the COVID-19 crisis. The results illustrate the power of collective foresight approaches to provide timely, nuanced insights for decision-making across sectors and scales, particularly in times of uncertainty.